158k views
3 votes
I have attached a picture of the question.​

I have attached a picture of the question.​-example-1

1 Answer

1 vote

Answer:

B: 1

Explanation:

I'm not sure what kind of given information that is, but here is my explanation:

f(x) = g(x) and values for both are given, so we combine their contents into one function: 3 - 6x = 5x - 8. Add 6x on both sides then add 8 on both sides, that'll get you 11x = 11. Divide both sides by 11 and you'll get x = 1.

User Krisanalfa
by
5.7k points